[Filling the rum casks] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Mechanism used to fill wooden casks containing the rum, in fact the photo shows a worker filling the wooden casks directly from the still.
Cataloger's title
Keywords: Rum -- Trinidad and Tobago; Barrels; Distillery warehouses -- Trinidad and Tobago